Inheritance of resistance to bud fly infestation in linseed (Linum usitatissimum L.) - Singh, P.K.; Sumit, Sumit; Yadav, D.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic analysis was carried out to determine the mode of inheritance of resistance to bud fly which is a key pest of linseed during flowering stage. Parents, F1, F2, BC1 and BC2 populations of three crosses involving two resistant, IC 15888 and JRF4 and two susceptible parents, viz., Neelum and GS-41 were the experimental materials. Reaction to bud fly in F1s of all the three crosses indicated that resistance was dominant over susceptibility. The F2 and back cross segregants were categorized in to resistant and susceptible classes based on per cent bud infestation. The genetic analysis in F2 generation revealed that two dominant complementary genes in IC 15888 control the bud fly resistance, while JRF 4 carried a single dominant gene for resistance. The F2 results were confirmed by genetic analysis of back cross populations. It can be categorically stated that the knowledge of number and nature of resistance genes in IC 15888 and JRF4 will be valuable for development of bud fly resistant varieties in linseed.